Mangaba (Hancornia speciosa Gomes) fruit juice decreases acute pulmonary edema induced by Tityus serrulatus venom: Potential application for auxiliary treatment of scorpion stings. (May 2020) - de Oliveira Yamashita, Fabiana; Torres-Rêgo, Manoela; dos Santos Gomes, Jacyra Antunes; Félix-Silva, Juliana; Ramos Passos, Júlia Gabriela; de Santis Ferreira, Leandro; da Silva-Júnior, Arnóbio Antônio; Zucolotto, Silvana Maria; Fernandes-Pedrosa, Matheus de Freitas
Abstract: Scorpionism represents a serious public health problem due to its increasing incidence. In Brazil, Tityus serrulatus is a species of major medical importance, especially in children and the elderly, as envenomation may induce serious acute pulmonary edema. "Mangaba" ( Hancornia speciosa Gomes) fruit juice is popularly used in the treatment of several inflammatory disorders. The objective of this study was to analyze the chemical composition of fruit juice of H. speciosa by HPLC-DAD-MS/MS, as well as to evaluate its anti-inflammatory potential and antioxidant activity, and analyze the biochemical and hematological parameters in acute pulmonary edema induced by T. serrulatus venom (TsV) in mice . Mice were challenged with TsV (30 μg/kg, subcutaneously) and were treated with dexamethasone (2 mg/kg, intraperitoneally) or fruit juice (pre- or post-treatment protocols, by intra-gastric route at 100 and 200 mg/kg), and 2 h later were anesthetized for blood, lung, and kidney collection, for several biochemical analyses. Results showed that the juice decreased edema, myeloperoxidase levels, vascular permeability, and production of cytokines (IL-1β, IL-6, and TNF-α) in lung tissue. Also, the juice reduced the concentration of nitrite and malondialdehyde oxidative stress markers in renal tissue. Amylase, lactate dehydrogenase, aspartate aminotransferase, and creatine kinase seric levels were reduced when the animals were treated with the juice. HPLC-DAD-MS/MS analysis identified 13 phenolic derivatives. The results suggest that the juice was able to decrease the inflammatory effects induced by T. serrulatus, demonstrating that the use of juice can be relevant for the treatment of scorpion stings. Highlights: Thirteen phenolic derivatives were identified in Hancornia speciosa fruit juice. The ability of fruit juice to inhibit the inflammatory effects of Tityus serrulatus scorpion venom was evaluated. The juice decreased edema, MPO levels, vascular permeability, and production of cytokines in lung. The juice reduced the concentration of nitrite and malondialdehyde in kidney. These components should be responsible, at least in part, for the anti-inflammatory and antioxidant effects of the juice.